The role of side hustles on the professional development of full-time workers in Tacloban City - Abella, Anellerex A.; Marco, Jonathan R.; Medalla, Ma. Jamelle D.
The work landscape has evolved significantly, especially due to the COVID-19 pandemic, which reshaped work globally. Traditional 8-to-5 jobs have given way to more flexible working arrangements, leading to the rise of side hustles or gig economy activities. Side hustles, income-generating endeavors performed alongside full-time jobs, have become increasingly common. Despite concerns that side hustles might conflict with full-time work performance and be perceived to only contribute financially, this study argues that there is significance in the contributions of side hustles towards the professional development of full-time workers. The research focuses on the relationship between side hustles and professional development among full-time workers in Tacloban City, Philippines, where the gig economy is thriving yet unfamiliar. The study extracts insights from the lived experiences of full-time workers engaged in side hustles, revealing this phenomenon's unique contributions and challenges. This study found that there is a wide variety of side hustles full-time workers in Tacloban City engage in, these side hustles provide unique and multifaceted contributions that belong to a spectrum of significance highly dependent on the distinct perception of every side hustler. The findings of this study are limited to the locality of Tacloban City, further research involving other localities will aid in capturing the side hustle phenomenon thriving in the Philippines.